Purification of functional mouse skeletal muscle mitochondria using percoll density gradient centrifugation - Rea Victoria P. Anunciado-Koza; Anyonya R. Guntur; Calvin P. Vary; Carlos A. Gartner; Madeleine Nowak; Robert A. Koza (BMC Research Notes, 2023)
Abstract Objective Our goal was to isolate purified mitochondria from mouse skeletal muscle using a Percoll density gradient and to assess bioenergetic function and purity via Seahorse Extracellular Flux (XF) Analyses and mass spectrometry. Results Mitochondria isolated from murine quadriceps femoris skeletal muscle using a Percoll density gradient method allowed for minimally contaminated preparations with time from tissue harvest to mitochondrial isolation and quantification in about 3–4 h. Percoll purification from 100 to 200 mg fresh tissue yielded ~ 200–400 ug protein. Mitochondrial bioenergetics evaluated using the Seahorse XFe96 analyzer, a high-throughput respirometry platform, showed optimum mitochondrial input at 500 ng with respiratory control ratio ranging from 3.9 to 7.1 using various substrates demonstrating a high degree of functionality. Furthermore, proteomic analysis of Percoll-enriched mitochondria isolated from skeletal muscle using this method showed significant enrichment of mitochondrial proteins indicating high sample purity. This study established a methodology that ensures sufficient high quality mitochondria for downstream analyses such as mitochondrial bioenergetics and proteomics.